Prevalence of on time administration of carbapenem and its impact on PK/PD target attainment in hospitalized patients: a multicenter retrospective study - Song, Jin; Pang, Xiaoping; Chen, Huadong; Zhang, Ping; Ying, Miaofa; Xu, Renai; Yu, Zhenwei (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveOn time administration of carbapenem is important, but there are few data concerning the prevalence of timeliness and its impact on pharmacokinetic/pharmacodynamic (PK/PD) target achievement in hospitalized patients.MethodsThis was a multicenter retrospective study. Inpatients who received imipenem or meropenem for more than 3 consecutive days were included according to preset criteria. Patient information and dosing information were collected. The actual administration intervals were compared to the scheduled intervals, and those within a 1-hour error interval were defined as standard time window administration (STWA); otherwise, they were defined as noncompliant time window administration (NTWA). The 100% fT>MIC and 100% fT>4×MIC targets were applied for PK/PD target attainment analysis. A multivariable logistic regression model was used to identify independent risk factors associated with timely administration and the PK/PD target attainment rate.ResultsA total of 474 patients and 1,372 actual administration intervals were included in this study. Among these patients, 82 had drug concentration data and were analyzed for PK/PD target attainment. A total of 427 dosing intervals (31.12%) complied with the standard time window and were STWA, whereas 945 (68.88%) were NTWA. Weekend, night shift, and scheduled dosing intervals were found to be independent influencing factors for STWA. STWA was an independent influencing factor for the 100% fT>MIC and 100% fT>4×MIC target attainment rates.ConclusionOur results indicate a low rate of on time carbapenem administration. The on time carbapenem administration was a risk factor for PK/PD target attainment and should be well controlled in clinical practice.